Complete convergence and complete moment convergence for maximal weighted sums of extended negatively dependent random variables under sub-linear expectations - Mingzhou Xu (AIMS Mathematics, 2023)
In this article, we study the complete convergence and complete moment convergence for maximal weighted sums of extended negatively dependent random variables under sub-linear expectations. We also give some sufficient assumptions for the convergence. Moreover, we get the Marcinkiewicz-Zygmund type strong law of large numbers for weighted sums of extended negatively dependent random variables. The results obtained in this paper generalize the relevant ones in probability space.